The Effect of Special Exercises on the Most Superior Mental Processes and the Performance of Some Offensive Skills for Table Tennis Beginners - Muhammad Salman Jaber Al-Khuzai1 , Haider Flayeh Hasan2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research aims to prepare special exercises in developing some mental processes and performanceOffensive skills of table tennis for players and learn about the impact of special exercises in developingsome mental processes and performance of offensive table tennis skills for players. The researchers usedthe experimental approach in a way (equal groups) on the young players in the specialized school of tabletennis in the province of Najaf for the season (2018-2019) and adult the number of them is (20) players.The researchers concluded the effect of special exercises prepared by the researchers, permissions that itwas effective in developing the mental processes under discussion and performing basic table tennis skillsfor players, which makes it clear in the level of skill performance of the members of the experimentalgroup. The researchers took into account the characteristics of the players It has achieved positive resultsin increased capacity to develop for mental operations and the performance of basic table tennis skillsfor players. The researchers recommended that special exercises should be used from the stomach beforeresearchers’ developmental processes and perform basic table tennis skills for players.